Assessment of the Impact of the Digital Economy on Labor Resources Transformation in Kazakhstan - S. A. Kaliyeva; A. F. Maxyutova; R. U. Rakhmetova; S. E. Alpeissova (Экономика: стратегия и практика)
The present paper analyzed the impact of the digital economy and innovations on Kazakhstan’s labor resource transformation from theoretical and empirical perspectives. By means of correlation analysis the factors that were the most significant for the result variable - the employed population in high-tech and knowledge-intensive sectors of the economy were determined (R2>0,8). However, the correlation analysis revealed the multicollinearity - close linear relationship between all factors. In this regard, the method of statistical equations of dependencies was applied for further research. During the study, a multifactorial equation of dependencies was calculated. Key socio-economic factors influencing population employment in high-tech and knowledge-intensive sectors of the economy were determined. The degree of influence of each factor on the result variable was calculated. Thus, the level of employment in high-tech and knowledge-intensive industries of Kazakhstan is most influenced by four key factors: the share of Internet users, the degree of influence of this indicator is the most significant and amounted to 38.28%; the share of computer users – 28.27%; gross domestic product per capita - 19.47%; and internal expenditure on research and development work – 11.69%. Taking into account the fact that the digital innovation era today is almost at the very beginning of its development, the digital processes occurring in the economy, in particular in the labor market, require monitoring and in-depth analysis for the timely development of management levers and control of their impact, that only emphasizes the relevance of this study.